YouTube as an Alternative Learning Media for Independent Bilingual Young Learners: A Review - Ida Ayu Putu Anugrah Widiantari; Ni Luh Putu Eka Sulistia Dewi (Journal of English Teaching, 2023)
This study was designed to review the literature on the implementation of YouTube as the alternative learning media in English Language Teaching for bilingual young learners, which includes (1) identifying the effectiveness of using YouTube for independent bilingual learner; (2) YouTube in enhancing English language skills; and (3) providing suggestions for choosing the teaching strategy and media applying YouTube for Independent Bilingual Learner. This study employed a systematic review method to critically observe the application of YouTube as a digital learning medium for independent bilingual learners. Data collection was carried out through a systematic review of 45 articles with several predetermined categories related to the use of YouTube. The research findings implied the effectiveness of using YouTube as an alternative medium for young bilingual learners during the Covid-19 pandemic. It was also revealed that from the results of the literature review, the use of YouTube could affect students’ language skills. In addition, the use of YouTube also affected self-motivation and self-regulated learning for bilingual young learners. This study also provided suggestions for teachers to pay attention to several things in using YouTube as an alternative media in ELT during the current pandemic.